Motivation : The Right Step to Success (Simply Knowing It) - Kumar, Gajendra (Journal of Commerce and Trade, 2008)
Motivation is the driving force that impels people to action. Motivation brings the immense confidence that is the basis of success. The motivated and inspired people gain much success and name in life. Motivation lays foundation to achievement and the best utilization of capabilities in sum up it is the secret of success and inspiration for every achievement. It is the effort to bring success.